Evaluation of eugenol toxicity in bioassays with test-organisms - Juliano Santos Gueretz; Cleder Alexandre Somensi; Maurício Laterça Martins; Antonio Pereira de Souza (Ciência Rural, 2017)
ABSTRACT: Fish in both natural and farming conditions are exposed to stress of capture, handling, transport or treatment that provoke low zootechnical performance. Anesthetics like eugenol obtained from clove oil have been used strategically not only in freshwater but also in marine and estuarine fish in order to reduce the stress. Apart from the eugenol indication as anesthetic and its low toxicity for animals, its environment action is not clear. Bioassays or ecotoxicity tests with indicator organisms are used to evaluate the mode of action of the pollutants in the environment. The aim of this study was to test the acute toxicity of eugenol using the microcrustacean Daphnia magna and the bacterium Aliivibrio fischeri, and also its chronic toxicity for the algae Desmodesmus subspicatus. Eugenol in the concentrations of 50, 75 and 100mg L-1 were toxic to tested indicator organisms.